Clinical Significance of Pain in Differential Diagnosis between Spinal Meningioma and Schwannoma - Dorota Olex-Zarychta (Case Reports in Oncological Medicine)
While common MRI characteristics for schwannomas exist, diagnosis by imaging alone remains challenging. Detailed analysis of symptoms reported by the patient is very important in the differential diagnosis between meningioma and schwannoma in cases where MRI images are not sufficient for determining the tumor type. The pain, its classification of the character, and the timing seem to be an important predictive symptom in the differential diagnosis of spinal schwannoma.